PENGARUH RESTRUKTURISASI ORGANISASI, KEPEMIMPINAN DAN KOORDINASI TERHADAP EFEKTIVITAS KERJA DI SEKRETARIAT DAERAH KABUPATEN KUTAI TIMUR - Mitha Ferdina (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This research is aimed to know the influence of restructuring the Organization, leadership and coordination both individually or collectively to the effectiveness of the work of civil servants in the Secretariat of the East Kutai Regency. The type of this research is a associative quantitative one. The techniques used in determining the sample was proportional random sampling by the method of probability sampling. Level of trust in this research by 90 % or ᾱ 10 %, whereas the sample set as many as 78 people using the formula Slovin. Data analysis techniques used to use regression analysis, correlation product moment f-test and t-test.